Behavioural economics, what have we missed? Exploring "classical" behavioural economics roots in AI, cognitive psychology, and complexity theory - Steve J. Bickley; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
In this chapter, we ask (conceptually and methodologically) what exactly is behavioural economics and what are its roots? And further, what may we have missed along the way? We argue that revisiting "classical" behavioural economics concepts and methods will benefit the wider behavioural economics program by questioning its yardstick approach to 'Olympian' rationality and optimisation and in doing so, exploring the 'how' and 'why' of economic behaviours (micro, meso, and macro) in greater detail and clarity. We also do the same for fields which share similar ontological and epistemological roots with "classical" behavioural economics. In particular, cognitive psychology, complexity theory, and artificial intelligence. By engaging in debate and investing thought into multiple layers of the ontology-epistemologymethodology, we look to engage in 'deeper' (and potentially more profound) scientific discussions. We also explore the utility and implications of mixed methods in behavioural economics research, policy, and practice.
Keywords: 330; Behavioural Economics; Cognitive Psychology; Complexity Theory; Artificial Intelligence